Critical and Strategic Raw Materials for Energy Storage Devices - Maham Mahnoor; Rabia Chandio; Anum Inam; Inam Ul Ahad (Batteries)
The performance and scalability of energy storage systems play a key role in the transition toward intermittent renewable energy systems and the achievement of decarbonization targets through means of resilient electrical grids. Despite significant research and technology advancements, the scalability of innovative energy storage systems remains challenging due to the scarcity of raw materials (used for the production of energy storage media, cathodes, anodes, separators, conductive agents, and electrolytes). The European Commission has identified certain raw materials as both economically important and subject to supply risks, designating them as critical and strategic raw materials. In this review, a comprehensive analysis is conducted regarding 28 raw materials and rare earth elements which are essential for the production of batteries, supercapacitors, and other storage systems, emphasizing their criticality, strategic importance, supply chain vulnerabilities, and associated environmental and social impacts. This study also addresses potential substitute materials for energy storage devices and innovations that make these devices recyclable. Future trends are briefly discussed, including advancements in alternative chemistries and innovations to improve energy density in advanced batteries and supercapacitors, paving the way for hybrid energy solutions.